Morphological and pathogenic variability of Macrophomina phaseolina (Tassi.) Goid. incitant of Charcoal rot of maize in India - LOKENDRA SINGH and RAM DUTTA, MEENA SHEKHAR*, R.C. SHARMA (Indian Phytopathology, 2006)
Seven isolates of Macrophomina phaseolina incitant of charcoal rot of maize, obtained from different agro-ecological zones of India, varied in their cultural characteristics and pathogenic behaviour. On the basis of colony colour, isolates were divided in to four groups i.e. grayish white, blackish gray, dark black in centre periphery cremish and cottony white colour. Hyderabad isolate produced highest number of sclerotia (180.3 sclerotia/9 mm disc and 52.0/ microscopic 10X field) of bigger size (95.7Âµm), whereas Coimbatore isolate produced minimum number of slcerotia (169 sclerotia) that too with smaller size (66.9 Âµm). On the basis of sclerotial morphology, two groups of isolates could be formed, the one with oblong shape having irregular edges and the other being round with regular edges. On the basis of disease expression the Hyderabad isolate was observed to be most virulent by giving maximum disease (8.8) while Coimbatore isolate was found to be least virulent as it exhibited a highest rating of 5.2 in the susceptible inbred CM 120 on a scale of 1-9. The noteworthy observation of the study was that sclerotial size and number had positive correlation with virulence.